Panorama of terminology - Plested Álvarez, María Cecilia; Castrillón Cardona, Elvia Rosa (Íkala, Revista de Lenguaje y Cultura, 2004)
This paper presents a general view of terminology as a science, and a pointed view of terminology in Colombia. First, the origins of terminology are presented with the definitions proposed by som theoreticians This theoreticians' influence is fundamental in the development of that science. Then, modern terminological approaches are pointed out. Finally, the importance of terminology concerning the research applied to language for special purposes is discused as well as, terminology as the core of specialized communication and translation processes. Received: 27-02-04 / Accepted: 28-03-04 How to reference this article: Plested Álvarez, M. C. & Castrillón Cardona, E. R. (2004). Panorama de la terminologie. Íkala. 9(1), pp. 289 – 312